To what extent can dual inhibition of TRPV1 (Transient Receptor Potential Vanilloid-1) and PTGS2 (Prostaglandin- Endoperoxide Synthase 2) be achieved to alleviate pain in patients with refractory primary dysmenorrhea? - Yuqi He (Health and Molecular Frontiers, 2026)
Refractory primary dysmenorrhea remains challenging to manage because conventional therapies, particularly those targeting prostaglandin synthesis through PTGS2 inhibition, may provide insufficient pain relief in some patients. This study investigated the feasibility of dual inhibition of Transient Receptor Potential Vanilloid 1 (TRPV1) and Prostaglandin-Endoperoxide Synthase 2 (PTGS2) as a potential multi-target strategy for pain management in refractory primary dysmenorrhea. Molecular docking simulations were conducted to evaluate the binding affinities of two naturally derived compounds, Astragaloside IV from Astragalus membranaceus and ligustilide from Angelica sinensis, together with six newly designed derivative ligands. Protein structures were obtained from the RCSB Protein Data Bank, while ligand preparation and structural modification were performed using PubChem, ChemDraw Pro, PyMOL, and UCSF Chimera. AutoDock Vina was used to assess protein–ligand binding interactions with TRPV1 and PTGS2. The results showed no detectable binding interactions for Astragaloside IV and its derivatives under the present docking conditions. In contrast, ligustilide demonstrated stronger binding affinity toward TRPV1 and showed comparatively weaker binding toward PTGS2, while its first derivative exhibited potential binding interactions with both targets. Overall, ligustilide and its derivative showed greater potential for dual TRPV1/PTGS2 targeting than Astragaloside IV-derived compounds. However, the observed binding affinities remain insufficient for establishing effective dual inhibition, and further structural optimization and experimental validation are required. These findings identify ligustilide as a potential lead compound for future investigation into multi-target therapeutic strategies for refractory primary dysmenorrhea.